PENGARUH FINANCIAL DISTRESS, AUDIT LAG DAN SOLVABILITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Nevi Pradana Ramadhani (2023)
The purpose of this research is to determine, analyze and examine the effect of financial distress, audit lag and solvency on going concern audit opinions. This research is a quantitative descriptive research. This research used manufacturing companies that listed on the Indonesia Stock Exchange (IDX) in 2017-2021 as population. The data used comes from the IDX's official website. Data were analyzed using logistic regression analysis in the statistical analysis software, SPSS 26. The results show that financial distress has no significant effect on going concern audit opinions. Meanwhile, audit lag and solvency has a significant effect on going concern audit opinions